Selected Sanctions in Polish Social Assistance Law - Żołnierczyk, Ewa (University of Wroclaw. Faculty of Law, Administration & Economics, 2020)
The social assistance system is determined by the support of individuals and families in their efforts to meet the necessary life needs. The purpose of assistance is to prevent difficult life situations that individuals and families cannot overcome using their own rights, resources and capabilities. This assistance must be provided in accordance with legal rules, and in all cases where these rules are not met, it must be modified, for example applying sanctions, otherwise it would turn into widespread distribution of public money. The author undertook an analysis of selected sanctions, which are provided for in the Act of 12 March 2004 on social assistanceThe Act of 12 March 2004 on social assistance (Journal of Laws 2019, item 2473), reaching conclusions on the advisability and necessity of their application on a practical basis.
Keywords: pomoc społeczna; sankcja; zwrot nienależnie pobranych korzyści; unieważnienie lub zmiana decyzji; cofnięcie zezwolenia